The Role of Elements in Visual Merchandising on Impulsive Buying in Retail Stores (Study on SW Market Stores in Bantul) - Liliyan, Aditya (Journal of Social Science and Business Studies, 2024)
This study aims to examine the influence of elements in visual merchandising on impulsive buying behavior at a minimarket called SW Market. Visual merchandising, which includes store layout, product display, and employee interaction, is considered important in influencing impulsive buying.  We collected data from 190 respondents who had recent shopping experiences at a minimarket using a survey approach and a Likert-scale questionnaire. The results show that a well-structured store layout facilitates consumer navigation, while attractive product displays increase visual appeal and the desire to buy impulsively. In addition, positive interactions with employees create a pleasant shopping atmosphere and encourage spontaneous purchasing decisions. This study also found that the combination of the three elements has a significant synergistic impact on impulsive buying behavior. These findings provide practical implications for retailers to optimize visual merchandising strategies to improve shopping and sales experiences. This study contributes to the literature on consumer behavior with a focus on the unique dynamics of minimarkets in Indonesia.